Dopamine prevents lipid peroxidation-induced accumulation of toxic α-synuclein oligomers by preserving autophagy-lysosomal function - Jiang, Peizhou; Gan, Ming; Yen, Shu-Hui (Frontiers in Cellular Neuroscience, 2013)
The formation of Lewy bodies containing α-synuclein (α-syn), prominent loss of dopaminergic neurons and dopamine (DA) deficiency in substantia nigra and striatum are histopathological and biochemical hallmarks of Parkinson’s disease (PD). Multiple lines of evidence have indicated that a critical pathogenic factor causing PD is enhanced production of reactive oxygen species(ROS), which reacts readily with polyunsaturated fatty acids (PUFAs) to cause lipid peroxidation (LPO). LPO products have been shown to facilitate assembly of toxic α-syn oligomers in in vitro studies. Since DA is prone to autoxidation and cause ROS, it has been suggested that interactions among DA, LPO and α-syn play an important role in neuronal loss in PD. However, the exact mechanism(s) remains unclear. We addressed this issue using a neuronal cell model (referred to as 3D5/DAT) which inducibly expresses human wild-type α-syn by the tetracycline off (TetOff) mechanism and stably expresses high levels of dopamine transporter. Under retinoic acid elicited neuronal differentiation, cells with or without overexpressing α-syn and with or without exposure to LPO inducer--arachidonic acid (AA), plus 0 to 500 µM of DA were assessed for the levels of LPO, α-syn accumulation, cell viability and autophagy. AA exposure elicited similar LPO levels in cells with and without α-syn overexpression, but significantly enhanced the accumulation of α-syn oligomers and monomers only in cultures with TetOff induction and decreased cell survival in a LPO-dependent manner. Surprisingly, DA at low concentrations (<50 µM) protected cells from AA cytotoxicity and α-syn accumulation. Such effects were attributed to the ability of DA to preserve autophagic-lysosomal function compromised by the AA exposure. At high concentrations (>100 µM), DA exposure enhanced the toxic effects of AA. To our knowledge, this is the first report showing biphasic effects of DA on neuronal survival and α-syn accumulation.